Visible light induced enhanced photocatalytic degradation of industrial effluents (rhodamine B) using BiVO4 nanoparticles - Nguyen, Duy Trinh; Hoang, Ho Huy; Xuan Linh, Nong; Nguyen, Huu Vinh; Thi Vu, Hien; Thanh Nguyen, Hai; Do, Sy Trung; Vo, Dai-Viet N. (IOP Publishing, 2019)
This study investigates the photodegradation of the organic dye Rhodamine B (RhB) under visible light irradiation by BiVO4 photocatalysts synthesized hydrothermal method. A RhB solution (100 mL, 15 ppm) was degraded in 20 min using the BiVO4 photocatalysts with visible light irradiation. The effect of temperatures calcination on visible-light photocatalytic activity and light absorption performance of BiVO4 was discussed in details. The results showed that BiVO4 sample calcined at 450 °C exhibited the highest photocatalytic performance on the degradation of a Rhodamine B solution. The RhB degradation by the BiVO4 catalyst is 62.38% after 200 min of simulated solar irradiation.